2013
DOI: 10.1111/1471-0528.12199
|View full text |Cite
|
Sign up to set email alerts
|

A re‐evaluation of the role of rotational forceps: retrospective comparison of maternal and perinatal outcomes following different methods of birth for malposition in the second stage of labour

Abstract: Objective To compare the outcomes of operative cephalic births by Kielland forceps (KF), rotational ventouse (RV), or primary emergency caesarean section (pEMCS) for malposition in the second stage of labour in modern practise.Design Retrospective observational study.Population Data were included from 1291 consecutive full-term, singleton cephalic births between 2 November 2006 and 30 November 2010 with malposition of the fetal head during the second stage of labour leading to an attempt to deliver by KF, RV o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
102
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 46 publications
7
102
5
3
Order By: Relevance
“…We also note the high failure rate of rotational ventouse and feel that this cannot be tolerated given the worse neonatal outcomes associated with sequential instrument use and secondary cesarean section. 1 In summary these results reaffirm our clinical impression that Kielland forceps are the superior tool in the obstetricians' armamentarium.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…We also note the high failure rate of rotational ventouse and feel that this cannot be tolerated given the worse neonatal outcomes associated with sequential instrument use and secondary cesarean section. 1 In summary these results reaffirm our clinical impression that Kielland forceps are the superior tool in the obstetricians' armamentarium.…”
supporting
confidence: 67%
“…Tempest et al 1 conclude that the results of their study 'should encourage clinicians to re-evaluate their choice of instrument for rotational birth and professional bodies to re-consider training opportunities for this type of birth', and that within the UK, 'there are sufficient practitioners to allow a safe phased re-introduction of rotational forceps'. Although we would like to believe this is so, and trainees seem keen to learn, our survey suggests that, at least in our region, the cohort of trainers has declined so much that it may already be too late.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have concluded, as we do here in the full cohort analysis, that overall forceps delivery is more likely to achieve successful vaginal delivery than ventouse there is also evidence that operator preference for a particular instrument can affect the delivery outcome. [13][14][15][16][17] However, rotation of the fetal head is considered a controversial procedure by many obstetricians, despite data showing low complication rates. [18][19][20] Although more experienced accoucheurs had the highest unadjusted rates of unsuccessful instrumental attempts, this is likely to be because more difficult deliveries are usually handled by more senior obstetricians.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,11 Although instrumental vaginal deliveries are commoner in cases of VM, vacuum extraction is associated with higher failure rate than (Kielland's) forceps. 12,13 Manual rotation may correct the malposition. 10,14 No recent study to our knowledge has evaluated the outcome of labor in cases of VM in sub-Saharan women.…”
Section: Introductionmentioning
confidence: 99%